Occupational stress in physicians working in hospitals and outpatient clinics - Czabak-Garbacz, Róża; Stasiuk, Weronika; Zakrocka, Izabela Natalia; Cygan, Beata; Furtak, Iwona (Polish Journal of Public Health, 2012)
Introduction. Medical profession can be a source of satisfaction but also of great stress. The main stressors include responsibility for patients health and life, bureaucracy at work, long absence from home, constant readiness, multitasking, moral and ethical dilemmas.Aim. The aim of the study was to asses whether there is any influence of workplace specifics on doctors’ vulnerability to work-stressors, stress-symptoms and strategies of coping with stress.Material and methods. A group of 116 physicians – 56 from hospitals and 60 from outpatients clinics of Tarnow (Poland) were surveyed. Statistical analysis was carried out with the use of Chi-square test of independence.Discussions. The reforms in health service and insurance system, bureaucracy, atmosphere at work place, conflicts with co-workers and health risk were for hospital doctors significantly more stressful than for those working in outpatients clinics. Physicians in outpatients clinics experiencing stressful situations complained more often than their colleagues in hospitals about difficulties in concentration and diarrhoea whilst less frequently of heartburn. Watching TV, drinking alcohol and frequent travelling, were more often used as a stress antidote by hospital doctors.Conclusions. The work environment of Polish doctors independently of their work place is a source of great stress; however physicians employed in hospitals seem to be more sensitive to work-related stressors and more resistant to stressful situations in private life than their colleagues in clinics for outpatients. Additionally doctors’ stress symptoms and anti-stress methods used by them frequently resulted from the specific character of their workplace.